Kaidah الأمور بمقاصدها Dan Penerapannya Dalam Fikih Keluarga - Faishal Faishal; Mhd Amar Adly; Heri Firmansyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Fiqh rules are formulated based on general principles and can be applied in various contexts. With these rules, Islamic law still has unity and integrity in its principles even though there are variations in its application according to different circumstances and conditions. In the rules of jurisprudence, there are 6 basic rules, 5 of which are agreed upon and the 6th rule which is still disputed by scholars, namely. Al Yaqin la yuzal bi al-syak. Al-Masyaqqah tajlib al-Taysir. Al-Dhoror Yuzal. Al-'adah muhakkamah. And what is disputed is I'malul Kalam awla min Ihmalihi. This article aims to discuss one of the basic rules of al Umur bi Maqasidiha, the meaning, meaning of the rule, the origin of the rule and exceptions as well as the application of the rule of al Umur bi Maqasidiha in family jurisprudence. This research is a library research study. Primary data sources were obtained from literature and classical books of ulama related to the rules of al Umur bi Maqasidiha. According to this rule, every human word and action depends on the intention and intent of the perpetrator. So worship that is not based on good and correct intentions can invalidate the worship.